Development of Flashcard Media Based on Augmented Reality on Dynamic Fluid Material to Train Critical Thinking Skills of High School Students - Mutiara Putri; Irvan Nur Rizki; Leni Marlina; Sudirman; Murniati (Jurnal Penelitian Pendidikan IPA, 2024)
Based on challenges in physics education, complex and abstract fluid dynamics, improving critical thinking skills is crucial for 21st-century learning. Needs analysis of 59 XI SMA Negeri 2 Plus Banyuasin III students revealed 90% had never used AR-based flashcards and showed high interest. The study aimed to develop valid, practical, and effective augmented reality-based flashcards using Research and Development (R&D) methodology with the Rowntree model and Tessmer formative evaluation. The research process involved planning, development, and evaluation stages. Results demonstrated high validity across components: media (93.33%), material (93.32%), critical thinking skills (96.66%), language (97.77%), and design (100%). Practicality assessments showed 95.18% in one-to-one and 95.73% in small group evaluations. The media effectively enhanced critical thinking skills with an N-Gain of 0.71, indicating high potential for dynamic fluids learning in grade XI. Conclusively, the augmented reality-based flashcards proved valid, practical, and effective for physics education.